ANALISIS KESALAHAN MAHASISWA DALAM MENYELESAIKAN SOAL TEORI HIMPUNAN PADA MATA KULIAH HIMPUNAN DAN LOGIKA - Tuhfatul Janan; Pratiwi Dwi Warih Sitaresmi; Nuryami Nuryami (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This research aims to describe some of the mistakes made by students in solving set theory problems in the set and logic course. The method used in this research is descriptive qualitative. The subjects in this study were students of Tadris Mathematics STAI Muhammadiyah Probolinggo Semester I for the academic year 2021/2022. Data collection techniques used in this study were exams and interviews. Based on the results of the study, it can be concluded that the subject made 9 types of errors, namely errors in determining the value of a quadratic equation, registering members of a set, writing mathematical notation, writing down sets, writing down members of Cartesian product, determining the intersection of two sets, determining the Cartesian product of two sets, determining the difference of the two sets, and determining the value of a quadratic inequality.